2015
DOI: 10.1186/s12879-015-1168-5
|View full text |Cite
|
Sign up to set email alerts
|

A decade of norovirus disease risk among older adults in upper-middle and high income countries: a systematic review

Abstract: BackgroundNoroviruses (NoVs) are the most common cause of acute gastroenteritis (AGE) causing both sporadic and outbreak-associated illness. Norovirus (NoV) infections occur across all ages but certain sub-groups are considered at increased risk due to heightened transmission and/or symptom severity. Older adults are potentially at high risk of NoV-associated illness due to frequent outbreaks in long-term care facilities (LTCFs) and severe health outcomes following infection. Elucidation of NoV risk among olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 110 publications
(218 reference statements)
3
44
0
1
Order By: Relevance
“…Lindasay et al reviewed 39 studies on risk estimates of norovirus infection and found a high burden of the infection in all ages with the highest rates of hospitalization and death among the elderly [3]. Older people are at higher risk of norovirus-associated hospitalization, resulting in excess hospital stays and greater costs compared to young adults [3].…”
Section: Infection In Older Adults and In Ltcfsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lindasay et al reviewed 39 studies on risk estimates of norovirus infection and found a high burden of the infection in all ages with the highest rates of hospitalization and death among the elderly [3]. Older people are at higher risk of norovirus-associated hospitalization, resulting in excess hospital stays and greater costs compared to young adults [3].…”
Section: Infection In Older Adults and In Ltcfsmentioning
confidence: 99%
“…Lindasay et al reviewed 39 studies on risk estimates of norovirus infection and found a high burden of the infection in all ages with the highest rates of hospitalization and death among the elderly [3]. Older people are at higher risk of norovirus-associated hospitalization, resulting in excess hospital stays and greater costs compared to young adults [3]. The overall estimates of disease burden suggest that noroviruses are responsible for approximately 10–20% of gastroenteritis hospitalizations, 10–15% of gastroenteritis deaths, and ≥0.2% of all-cause mortality among older adults in upper-middle-income and high-income countries [9, 10, 11•, 12,13].…”
Section: Infection In Older Adults and In Ltcfsmentioning
confidence: 99%
See 2 more Smart Citations
“…NoV is a highly infectious and rapidly evolving RNA virus that is responsible for the majority of acute gastroenteritis cases around the world (160)(161)(162). There is no vaccine or therapeutic intervention available to prevent or control NoV infections.…”
Section: Foodborne Virusesmentioning
confidence: 99%